Exploration of the Implementation of Music Therapy into the Health Services: Lituanian Experience - Vilmante Aleksiene; Sigita Lesinskiene (Journal of Human Health Research, 2017)
Integration of music therapy into medical treatment facilities is very uneven in different countries. Scientific evidence of successful examples and sharing of good practices between countries is essential for the further development of music therapy and the improvement of the quality of complex medical services. The goal of this study was to analyse the situation of music therapy implementation into the health services in Lithuania. Analysis of historical background, legislation and overview on music therapy training has been made. Music therapy in Lithuania has gone through more than thirty years of development. Acqaintance and acceptance of music therapy as a relevant and fruitful component to the complexity of the existing medical services was long but successful process. Overview of current initiatives and achievements of the implementation of music therapy into clinical practice and research has shown promissing positive results in developmental pediatrics, psychiatry, special education, neurology, neonatology, oncology, somatic and preventive medicine, rehabilitation. The Music Therapy Master program in Lithuania is being implemented. Possibilities to use music therapy as an inovative service and resourse in various medical settings are in the process of the rapid growth. Collaboration involving music therapists in interdisciplinary teams would help to achieve a comprehensive, versatile patient-centered and health-centered complex service.
Keywords: music therapy